Decomposition and Nutrients Release Pattern of Leaves, Stems / Vines and Roots of Selected Leguminous and Non-Leguminous Plant Species: Decomposition of Leguminous and Non-Leguminous Plants - Oguntade, Oladele Abdulahi; Adeogun, Abideen Idowu; Tian, Guogiong; Adeoye, Gideon (Biological Sciences - PJSIR, 2012)